Antigen detection from urine of kala-azar cases by latex agglutination tes - Alam, M; Shamsuzzaman, AK; Musa, AK; Khan, AH; Mahmud, MC; Hossain, MA; Ahmed, AA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):22-7. The abstract of this article is available on the PubMed website